The Causal Relationship Between Volatility in Crude Oil Price, Exchange Rate, and Stock Price in India : GARCH Estimation of Spillover Effects - Lakshmanasamy, T. (Indian Journal of Research in Capital Markets, 2022)
The macroeconomic variable: crude oil price, gold price, exchange rate, inflation, and stock returns are highly volatile and are highly correlated to each other. The volatility in one market spills over to other markets. This paper examined the dynamic causality between crude oil price, exchange rate, and BSE Sensex and their volatilities in India. The daily data on macro variables for 14 years between January 2006 and March 2019 were used in the GARCH estimation of causal effects of volatility spillovers. The GARCH estimates showed that one market’s volatility and volatility spillover caused volatility and volatility spillovers in other markets in India. Crude oil price, exchange rate volatility, and volatility spillovers caused volatility in the BSE Sensex. The volatility in BSE Sensex was highly overdone by internal shocks of the stock market.